Comparison of Pancreatic Damage in Rats for Two Methods of Paraquat Administration - Yanxia Gao; Linlin Hou; Yibo Wang; Yan Zhang; Shoutao Zhang; Yi Li; Yanan Jiang; Changju Zhu; Tongwen Sun; Guoyu Duan; Ding Yuan (Frontiers Media S.A., 2021)
It is noted that elevated serum amylase levels suggesting pancreatic damage has an association with prognosis in PQ patients. This study aimed to determine whether PQ can cause pancreatic damage. The two conventional models (intragastric infusion (iG) and intraperitoneal injection (iP)) may exhibit different effects on the pancreas depending on whether or not they pass through the digestive tract. In this study, the rats were divided into four groups: the intragastric infusion group (PQ-iG, n = 45), intraperitoneal injection group (PQ-iP, n = 53), normal control group 1 (NC-iG, n = 6) and normal control group 2 (NC-iP, n = 6). Pancreatic damage was compared between groups using serum amylase activity assay, hematoxylin and eosin (H&E) staining, TUNEL assay, and transmission electron microscopy (TEM). Serum amylase levels in group PQ-iG were significantly higher than in group PQ-iP (p < 0.05). Examination of the H&E sections showed damage to the pancreas. Both experimental groups were displayed inflammatory infiltration within 9 h of PQ treatment. After 9 h, patchy necrosis was observed in group PQ-iP, when inflammatory infiltration was still the dominant pathology. Necrosis appeared and gradually worsened in group PQ-iG, in which necrosis was the dominant pathology. The TUNEL assay showed significantly higher numbers of apoptotic cells in the pancreas of PQ-groups than in the control NC- groups (p < 0.05). TEM showed expansive endoplasmic reticulum lumens and mitochondria swelling in the pancreas of the PQ-groups. It is concluded that both methods of modeling could cause pancreatic damage and the type and degree of damage would change over time. Note that pancreatic damage in group PQ-iG was more severe than that in group PQ-iP. Therefore, clinical practitioners should pay close attention to pancreatic damage caused by PQ, especially when the route of PQ administration was oral.